Treatment of Atypical Clots - Ageno, Walter (Hämostaseologie, 2022)
The term unusual site thrombosis refers to the occurrence of venous thromboembolism outside of the lower limbs and the pulmonary arteries. Unusual site thrombosis can virtually affect any venous segment, with the most common and/or clinically relevant sites including the upper limbs veins, the retinal veins, the splanchnic veins and the cerebral veins. Clinical features are obviously heterogeneous, while many predisposing factors are common, though with different prevalence among the various disorders. Antithrombotic therapy is prescribed to most patients, but the type, intensity, and duration of treatment vary both within and among patient groups. Increasing evidence is supporting the use of the direct oral anticoagulants in patients with upper limb deep vein thrombosis, cerebral vein thrombosis, and with splanchnic vein thrombosis. This article will review available evidence on the treatment of venous thrombosis occurring in unusual sites.
Keywords: venous thrombosis; unusual site thrombosis; anticoagulation; direct oral anticoagulants